People's Perceptions of Tongke-Tongke Village East Sinjai District against Muhammadiyah - Jusniaty Jusniaty; Baharuddin Baharuddin; Muhammad Takdir (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
This organization was originally a socio-religious movement, and finally the goal of political space, namely by becoming a special member of Masyumi Persyarikatan Muhammadiyah is a very large Islamic organization and has spread to all corners of the country. So it is interesting to study the perception of the community, especially the people of Tongke-Tongke Village towards Muhammadiyah.This study aims to determine the perception of the people of Tongke-Tongke Village towards Muhammadiyah and what factors influence it. The research method used is descriptive qualitative. This research was funded by the Research Grant Program Batch V of the PP Muhammadiyah Diktilitbang Council in collaboration with the University of Muhammadiyah Sinjai. Data collection techniques through observation, interviews, documentation, and dissemination of google forms to reach respondents who are far away and find it difficult to arrange time to meet. The data analysis was carried out through the steps of data collection, data presentation, data analysis and drawing conclusions. The results of this study indicate that there is little response to knowledge of Muhammadiyah by the people of Tongke-Tongke Village, this is because they are not cadres who have gone through organizational recruitment, however, they are the general public or sympathizers who basically become part of several activities that have been carried out by Persyarikatan Muhammadiyah. This research can be used as a reference in making decisions about how the community responds and perceives the Muhammadiyah organization at the village level because previous research has focused on the sub-district level.